1980
DOI: 10.2307/3898428
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Feed Intake and Liveweight Change of Beef Cattle on a Mixed Tree Savanna in the Transvaal

Abstract: This study was conducted as part of a broad ecosystem project to identify and quantify some of the significant relationships between cattle and their environment. Over a period of 1 year, monthly measurements were made of Africander cattle ranging on mixed tree savanna in the Transvaal, Republic of South Africa. The following data were obtained: feed intake, liveweight change, crude protein content (CP) and digestibility of the diet, as well as the time which was spent feeding and mean bite size. Both CP and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…1) were generally similar to the patterns of treatment differences in forage intake (Fig. 2), suggesting that food intake primarily influenced cattle performance, as has also been reported by other studies (Zimmermann, 1980;Meissner, 1995;Odadi et al, 2011b).…”
Section: Discussionsupporting
confidence: 86%
“…1) were generally similar to the patterns of treatment differences in forage intake (Fig. 2), suggesting that food intake primarily influenced cattle performance, as has also been reported by other studies (Zimmermann, 1980;Meissner, 1995;Odadi et al, 2011b).…”
Section: Discussionsupporting
confidence: 86%
“…With a similar magnitude of increase in forb content of cattle diets, Judkins et al (1987) reported substantial increases in dietary crude protein (10.4%-12.6%), dry matter digestibility (42%-48%) and particulate passage rate (3.4%/h-3.9%/h) on a blue grama rangeland in New Mexico. Similarly, in a south African savanna, an increase in cattle diet forb content from 4% to 12% was enough to increase dietary crude protein from 5.9% to 11.1%, and organic matter digestibility from 55% to 63% (Zimmermann 1980;Skinner et al 1983). .…”
Section: Discussionmentioning
confidence: 97%
“…Forbs are generally known to have a much more rapid rate of digestion and higher passage rate than grasses (Kothman 1980;McCollum and Galyean 1985). During periods of relatively low grass quality, utilization of forbs may be important to bulk-feeding ruminants like cattle in enhancing their digesta fermentation and passage rates, leading to extended feeding time and higher overall intake (Zimmermann 1980;Skinner et al 1983;McCollum and Galyean 1985;Beekman and Prins 1989). Because cattle diet quality and digesta kinetics were not analyzed in this study, the actual nutritional changes associated with the observed 7%-9% difference in use of forbs by cattle among plots (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protein content of acacia and other browse species is also much higher than that of many native grasses found on the same land at the same time (Torres 1983). Studies have shown that for livestock production systems based on rangelands in arid and semi-arid regions, dietary protein is the limiting factor affecting liveweight gains (Prachett et al 1977;Zimmerman 1980;McKay and Frandsen 1969;Ward 1975). In addition, the seasonal peak of protein availability for A. albida occurs in the mid to late dry season when most extensive pastoral production systems suffer severe protein deficiency (Miehe 1986).…”
Section: Acacia Albida and Pastoralismmentioning
confidence: 99%